MBS : The Rise to Power of Mohammed Bin Salman - Hubbard, Ben (London WILLIAM COLLINS, 2020)
A Financial Times Book Best Book of the Year 2020 A Foreign Affairs Best Book of the Year 2020 The gripping, untold story of how Saudi Arabia's secretive and mercurial new ruler rose to power.
Include Color Illustrations and index
Keywords: Saudi Arabia -- Politics and government -- Social conditions -- International relations